Evaluation of Quality and Some Agronomic Traits of Bread Wheat (Triticum aestivum L.) Lines and Cultivars under Kahramanmaraş Ecological Conditions - Yücel, İ.; Başkonuş, T.; Dokuyucu, Tevrican; Akkaya, Aydın; Güngör, H.; Dumlupınar, Z. (Centenary University, 2022)
In this study, eight promising advanced bread wheat genotypes derived from breeding programs and Ceyhan-99, Sagittario, Masaccio, and Seri-82 commercial cultivars were used as materials. The experiments were carried out in 2018-2019 and 2019-2020 cropping years in a randomized complete block design with four replications. In the study, some agronomic and quality traits were investigated. Bread wheat genotypes varied significantly for all investigated traits in terms of the year, genotype, and year x genotype interactions. Based on average data, the investigated traits were determined as; plant height (PH) 90.86 cm, spike length (SL) 9.40 cm, spikelet number (SN) 18.90, grain number per spike (GNS) 56.22, grain weight per spike (GWP) 1.95 g, thousand kernel weight (TKW) 34.90 g, grain yield (GY) 654.54 kg/da, test weight (TW) 76.17 kg/hl, protein ratio (PO) 12.28%, wet gluten (WG) 34.16% and Zeleny sedimentation (ZS) 33.87 ml. According to the two-year results, the highest PH (102.8 cm) was obtained from the Ceyhan-99 cultivar, while ZDEB106 genotype had the longest spike length (9.83 cm) and the highest spikelet number (19.93). ZDEB108 genotype had the highest values in GNS (63.25), GWS (2.24 g), and test weight (77.73 kg hl-1 ). On the other hand, ZDEB103 genotype was the highest in PO (14 %), WGR (44.28 %) and ZS (40.78 ml). Again, ZDEB101 genotype had the highest TKW (39.255 g), while the highest grain yield (754.56 kg da-1 ) was obtained from the Massacio cultivar. On the other hand, principal component (PC1 and PC2) analysis explained 62.4 % of the total variation. Thus, a positive correlation was determined between GY with TKW, TW, and PH, while the other traits were negatively correlated with GY. © 2022, Centenary University. All rights reserved.
Bazı Ekmeklik Buğday (Triticum aestivum L.) Çeşitleri ve İleri Hatlarının Kahramanmaraş Ekolojik Şartlarında Tarımsal Özellikler ve Kalite Bakımından Değerlendirilmesi
Keywords: Bread wheat; Grain yield; Principal components analysis; Protein rate; Quality